Features of the Kazakh and Chinese arts and crafts. - Kenzhebaeva., A. A.; Kenzhebaeva., L. A. (Journal of Oriental Studies, 2016)
This article analyzes the developmental functions of arts and crafts of the Kazakh and Chinese peoples as an integral aesthetic, cultural, historical and socio-pedagogical phenomenon in terms of pedagogical practice. National forms, artgraphic methods, cultural and historical traditions, realities, customs of two nations are reviewed.